Analisis Problematika Pemanfaatan Artificial Intelligence (AI) Dalam Pembelajaran Pendidikan Islam Anak Usia Dini - Laila, Siti Nur; Enda, Mutiara; Nirwana, Evi Selva (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze in depth the various problems of using Artificial Intelligence (AI) in Early Childhood Islamic Education (ECI), specifically from the pedagogical, psychological, ethical, and understanding aspects of Islamic education. The research method used is a literature review by examining scientific books, national and international journal articles, and previous research results relevant to the themes of AI, early childhood education, and Islamic education. The results of the study indicate that the use of AI in ECI learning faces several problems, including limited teacher competence in using AI technology, the potential for reduced social and spiritual interaction of children, the risk of dependence on digital devices, and challenges in maintaining the role of teachers as Islamic educators. In addition, AI-based content does not fully guarantee alignment with Islamic moral and ethical values. Therefore, the use of AI needs to be carried out systematically, controlled, and proportionally so that it functions as a learning support tool without neglecting the main objectives of Early Childhood Islamic Education.